Identification of Fusarium wilt-resistant sources of long-duration pigeonpea (Cajanus cajan) - SINGH, FARINDRA; SINGH, I P; MAZUMDER, N D (The Indian Journal of Agricultural Sciences, 2011)
Present investigation was carried out during 2000–10 to identify and develop the wilt resistant donors of long duration pigeonpea [Cajanus cajan (L.) Millsp.]. Four long duration pigeonpea genotypes, viz IPA 16 F, IPA 8 F, IPA 9 F and IPA 12 F possessing acceptable yield levels were evaluated for their reaction to wilt disease in wilt sick plots continuously for three to five years at hot spots in north east plain zone, central zone and south zone of the country. All the four genotypes showed resistant to moderately resistant reaction to wilt over the years at all the hot spots. The consistency in the reaction (resistant to moderately resistant) to wilt disease indicated that genotypes IPA 16 F, IPA 8 F, IPA 9 F and IPA 12 F are very good source of resistance to all the five variants of Fusarium udum prevalent in India causing wilt and can be used as resistant donors in pigeonpea wilt resistance breeding programme.